In-Situ Variability of DOM in Relation with Biogeochemical and Physical Parameters in December 2017 in Laucala Bay (Fiji Islands) after a Strong Rain Event - Koliyavu, Timoci; Martias, Chloe; Singh, Awnesh; Mounier, Stéphane; Gérard, Philippe; Dupouy, Cecile (Journal of marine science and engineering, 2021)
Heavy rain events alter the biogeochemical outflows, affects water quality and ecosystem health within the coastal waters of small Pacific Islands. We characterized snapshots of the optical fingerprints of dissolved organic matter (DOM) sources together with the select nutrients, biogeochemical and physical variables for 10 stations in December 2017 in Laucala Bay, Fiji Islands. DOM absorption coefficients and fluorescence components were determined via spectrofluorometry and Parallel Factor Analysis identifying four components: Type M, two terrestrial (humic, fulvic) components, and a protein component linked to marine biological activity. Associations of DOM together with climate variables and the other tested variables were determined via principal component, hierarchical cluster, and cross-correlation (Pearson) analysis. All component s (together with most tested variables) displayed higher values (plumes) at the southwest coast consistent with surface currents outflow during the wet season. Type M component associated with two allochthonous fluorescent components signaling anthropogenic forcings via riverine outflows. Terrigenous inputs association with autochthonous chromophoric dissolved organic matter (CDOM) is indicative of tidal mixing, dilution, and bottom resuspension processes. Positive correlations of dissolved organic carbon (DOC) with nutrients (NOx, PO4) elucidates DOM being utilized as energy sources. The positive correlation of DON with nutrients (NOx, PO4, Si(OH)4) reflects the role of DON as a nutrient source consistent with chlorophyll plume formation.